2014
DOI: 10.1016/j.molonc.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor‐mediated cell death is distinct from its global effect on chromatin

Abstract: Romidepsin and vorinostat are histone deacetylase inhibitors (HDACis) that have activity in T-cell lymphomas, but have not gained traction in solid tumors. To gain deeper insight into mechanisms of HDACi efficacy, we systematically surveyed nineteen cell lines with different molecular phenotypes, comparing romidepsin and vorinostat at equipotent doses. Acetylation at H3K9 and H4K8 along with 22 other histone lysine acetylation and methylation modifications were measured by reverse phase proteomics array (RPPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
(58 reference statements)
1
43
0
Order By: Relevance
“…Treatment with romidepsin or SAHA for 6 h caused similar increases in histone acetylation in all cell lines, but not all of the cell lines underwent apoptosis upon romidepsin or SAHA treatment. Therefore, the effects on histone acetylation did not correlate with effects on apoptosis in all cell lines [111]. In summary, recent research indicates that HDACiinduced changes in histone acetylation cannot (fully) explain their effects on gene expression and apoptosis.…”
Section: From Histones To Transcription Factorsmentioning
confidence: 82%
See 1 more Smart Citation
“…Treatment with romidepsin or SAHA for 6 h caused similar increases in histone acetylation in all cell lines, but not all of the cell lines underwent apoptosis upon romidepsin or SAHA treatment. Therefore, the effects on histone acetylation did not correlate with effects on apoptosis in all cell lines [111]. In summary, recent research indicates that HDACiinduced changes in histone acetylation cannot (fully) explain their effects on gene expression and apoptosis.…”
Section: From Histones To Transcription Factorsmentioning
confidence: 82%
“…Another study found that upon HDACi treatment there was a precisely timed increase in histone H3 lysine 27 trimethylation (H3K27me3) at transcription start sites, but little or no increase in histone acetylation, whose role seemed to be to provide a stable chromatin environment that allows transcription to be modified by other factors [110]. In another study, the nonselective HDACi romidepsin and SAHA were tested in different cancer cell lines, and their effects on histone acetylation were investigated together with their effects on apoptosis [111]. Treatment with romidepsin or SAHA for 6 h caused similar increases in histone acetylation in all cell lines, but not all of the cell lines underwent apoptosis upon romidepsin or SAHA treatment.…”
Section: From Histones To Transcription Factorsmentioning
confidence: 99%
“…Laboratory studies have shown that while there is a global increase in histone acetylation, this does not correlate with cell death, beyond a required concentration threshold (88). It can be argued that the effect on chromatin (i.e., global histone acetylation leading to gene transcription) should be considered separately from the events leading to cell death.…”
Section: Targeting the Epigenome In Ptclmentioning
confidence: 99%
“…In the laboratory, HDAC inhibitors can induce cell-cycle arrest, differentiation, or apoptotic cell death in cancer cells. Which effect is observed depends upon cell context and cell sensitivity (5). In 2002, when the phase I trial was published, we were mostly cognizant of the cell cycle and differentiating effects of the HDAC inhibitors.…”
mentioning
confidence: 99%
“…This meant that patients treated with romidepsin were receiving concentrations that were effective in laboratory models, and that mechanistic studies of the agent performed in the laboratory could be clinically relevant. Since then, we have observed that cell types that undergo a cell-cycle arrest in G 1 are actually on the less sensitive side of the spectrum, and that some cell types, such as T-cell lymphoma cells, undergo rapid cell death via apoptosis (5). The importance of the intrinsic apoptosis pathway in cancer cell death from romidepsin has now been clearly demonstrated, and efforts to identify combinations of agents that will enhance apoptosis are under way in several laboratories (6)(7)(8)(9).…”
mentioning
confidence: 99%